Effects of dark chocolate consumption on anxiety, depressive symptoms and health-related quality of life (HRQoL) among identified cancer patients in East Coast Peninsular Malaysia - Wong, Sok Yee (2012)
Anxiety and depressive symptoms are common among patients with cancer and have been shown to adversely affect their health-related quality of life (HRQoL). Essentially, the reduction of anxiety and depressive symptoms is expected to improve HRQoL status. The benefits of dark chocolate in alleviating mood and stress are becoming important in healthcare studies. This three-part study was conducted to investigate the 1) applicability, practicability, comprehensiveness, reliability and validity of the measurement instruments; 2) effects of dark chocolate comsumption on anxiety and depressive symptoms among healthy volunteers and 3) effects of dark chocolate consumption on anxiety, depressive symptoms and HRQoL status among patients with cancer. The first part comprised of a cross-sectional study at Hospital Sultanah Nur Zahirah (HSNZ), Kuala Terengganu. The Malay versions of Hospital Anxiety and Depression Scale (HADS) and McGill Quality of Life Questionnaire (MMQoL) were pilot tested among 80 patients with cancer. Results were supportive of favourable psychometric properties. The second part involved 20 healthy student nurses (cross-cover design) and another separate group of 47 similar respondents (parallel design) from Universiti Sultan Zainal Abidin. The intervention Group, IG (consumed 50g of dark chocolate) generated significantly more favourable outcomes compared to the Control Group, CG (consumed a local delicacy/mineral water) after three days. An additional validated Depression, Anxiety and Stress Scale (DASS-21) supported the findings shown by HADS. The final part employed a parallel, open-labelled study in 133 in-patients with cancer from public hospitals in Terengganu, Pahang and Kelantan. Both the validated Malay HADS and MMQoL were used. As before, dark chocolate (50g; 275 kcal) was administered to IG while CG respondents consumed mineral water for three consecutive days. Anxiety and depressive symptoms were again significantly reduced in IG at follow-up (all p < 0.05). Between groups, IG patients reported significantly improved Total MMQoL Score compared to CG patients (p < 0.001). The overall findings seemed to indicate that short-term dark chocolate consumption could possibly improve anxiety, depressive symptoms and HRQoL for patients with cancer. Nonetheless, due to several uncontrolled confounding factors susch as situational variables and consumer characteristics. Further extensive studies are necessary to support these findings before it could be recommended as a practical, non-pharmacological remedy for such patients.